Simulating the Effects of Personal Income Tax on Government's Tax Income and Income distribution - Ali Nasiri Aghdam; Ashraf Razmi (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2015)
In this paper, to evaluate income and distributional effects of Personal Income Tax, a hypothetical society is simulated. 12 income sources are defined that each member of society can earn income from one income source or more. Then, using FORTRAN programming, the government's tax income, income distribution and average tax rate are calculated, assuming five alternative Scenarios: 0. Base scenario: taxing personal income at source according to "Direct Income Taxes Act"; 1. taxing the sum of incomes each individual person earns from different businesses he or she owns and exempt his / her business income once; 2. taxing the sum of incomes each person earns from non-exempt sources and exempt his / her business income once; 3. taxing the sum of incomes each person earns from exempt and non-exempt sources and exempt his / her business income once; 4. qualifying third scenario by accepting a 1 billion Rials as exemption. Results of simulation indicate that the government's income and income equality is maximized in 3rd scenario.